2014
DOI: 10.1097/brs.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Altered Disc Compression in Children With Idiopathic Low Back Pain

Abstract: Study Design This study is a repeated measures design to measure the lumbar spine’s response to common backpack loads in children with idiopathic low back pain (ILBP) using upright MRI. Objective The purpose of this study is to analyze the lumbar spine’s response to backpack loads with upright MRI in ILBP children in order to compare their results to previously published normal child data under the same conditions. We hypothesize that typical backpack loads will have a different effect on the lumbar spine of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…All subjects walked on a treadmill with no bag, and while carrying a shoulder bag or backpack at the height of the iliac crest, 10 cm lower than the iliac crest, or 20 cm lower than the iliac crest 11 ) . The weight of the bag was set at 10% of the body weight of each subject 2 , 9 , 12 , 13 ) . The order of the tasks was carried out at random to prevent a carry over effect.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects walked on a treadmill with no bag, and while carrying a shoulder bag or backpack at the height of the iliac crest, 10 cm lower than the iliac crest, or 20 cm lower than the iliac crest 11 ) . The weight of the bag was set at 10% of the body weight of each subject 2 , 9 , 12 , 13 ) . The order of the tasks was carried out at random to prevent a carry over effect.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between pain and backpack weight per body mass index among girls was positive and significant, but negative and not significant among boys. The L4–L5 and L5–S1 intervertebral disc compress, particularly anteriorly, when transitioning from the supine to the upright position when carrying a 10% body weight backpack 9 ) . Al-Khabbaz et al 10 ) reported that the rectus abdominis muscle activity increased progressively and disproportionately as the backpack load increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 13‐year‐olds found that increasing backpack load did not change lumbar lordosis in either those with idiopathic low back pain or controls, but they noted that children with low back pain experienced significantly less lumbar lordosis with backpack load compared with controls but that it was unclear whether this related to their back pain (Shymon et al. ). These uncertainties indicate the need for a better understanding of the factors affecting the development of the lumbar lordosis.…”
Section: Introductionmentioning
confidence: 99%
“…The deleterious effect of backpack carriage on both children [1,2], and adults [3,4] alike has been a subject of growing interest and research. Findings from these studies and others indicate that backpack carriage may alter posture [1,3], may cause back pain [5] and increased exertion [4], and may have adverse effects on the cardiopulmonary system [6].…”
Section: Introductionmentioning
confidence: 99%